Fostering Students' Workplace Communicative Competence and Collaborative Mindset through an Inquiry-Based Learning Design - Rosa Huiju Chen (MDPI AG, 2021)
This paper illustrates the efficiency of implementing an inquiry-based teaching and learning module on the development of workplace communication competence and collaborative mindset in a college-level English as a Foreign Language context. In particular, the study highlights the 5E constructivist approach as the pedagogical foundation and addresses the effects of project-based learning scenario on students' engagement and their views in terms of "workplace habits of mind". The 5E model includes five stages: engagement, exploration, explanation, elaboration, and evaluation. In addition, teaching strategies like academia-industry cooperative teaching, industry field trip, reflective writing, and project-based presentation were incorporated into each instructional phase to emphasize the development of students' social, collaborative, and problem-solving skills. Both quantitative and qualitative data were collected including students' perceived effectiveness of engagement activities, weekly reflective journal writing and focus group interviews. The results of the study indicate that the inquiry-based teaching and learning approach had a favorable effect on the development of students' engagement and hands-on, mind-on skills such as critical thinking, collaboration, and communication.